AN ANALYSIS OF STUDENT’S MOTIVATION IN LEARNING ENGLISH - Umpung, Jervino Miraycle Daniel; Liando, Nihta V. F.; Andries, Fivy (SoCul: International Journal of Research in Social Cultural Issues, 2023)
Motivation is one of the keys to get achievement in learning. This study is designed to analyze students’ motivation in learning English. Specifically, this study focuses on finding out whether the students’ motivation is either integrative or instrumental. This study is conducted in the framework of mixed-method research in which the researcher used both qualitative and quantitative methods. SMP Berea Tondano is the location where the research is carried out. The data sources of this research are all the students at SMP Berea Tondano who lived at Etty Orphanage. To collect the data, the researchers uses a questionnaire consisting of 10 questions where 5 statements are to measure students’ integrative motivation and 5 questions for measuring their instrumental motivation. The data obtained are analyzed quantitatively and qualitatively. The findings reveal that the students have both integrative and instrumental motivation in learning English. This study further shows that students’ integrative motivation (with a mean score of 3.96) is higher than their instrumental motivation (with a mean score of 3.87). Motivation is an important part of the learning process. Because it affects the students’ attitudes, morals, and achievement in learning not just English but all the other subject.